Effect of annealing temperature on supercapacitive behaviour of hydrothermally synthesised ZnO nano-platelets. (2018) - Das, Arya; Sahoo, Rakesh Kumar; Singh, Saroj Kumar
ZnO nano-platelets have been prepared using a high pressure reactor via hydrothermal route and calcinated at different temperatures. The structure and morphology of the grown zinc oxide (ZnO) nano-platelets (NP) at different temperatures has thus been reported. Raman spectroscopy and X-ray diffraction (XRD) confirmed ZnO formation. The nano-platelets morphology was confirmed by scanning electron microscopy (SEM). The change in morphology and its adverse effect on the capacitive behaviour of the as-synthesised nano-platelets with change in calcinations temperature has also been discussed. The potential of these nano-platelets for possible applications in energy storing devices has been established.